ON TRANSPARENCY, WHAT IS BEING PROMISED BY THE POLITICAL PARTIES IN TURKEY IN THEIR GENERAL ELECTION MANIFESTOS? - Mahmut Doğan; İdris Sarısoy (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The purpose of this study, to determine the distribution of discourses-promises on transparency in election manifestos of political parties that passed the 10% election threshold in eight general elections according to the distinction of trend slopes, party ideology (right-left) and ruling, opposing party between 1991-2015 in Turkey. Although many qualitative and quantitative studies have been conducted in the literature on the effects of the processes and results of the transparency issue after 2000, there is no study encountered analyzing the transparency discourses-promises in the statements. 28 election manifestos were analyzed with content analysis method in terms of “discourse-promise of transparency”. As a result, 258 transparency discourse promises were identified. 146 of them are administrative, 84 are financial and 28 are political transparency. In administrative transparency, providing and obtaining information and the activities of public institutions; in financial transparency, use of resource and bids; in political transparency, in line with the expectations, the discourse-promise of transparency regarding the declaration of property of politicians has come to the fore. Although there is no difference between right and left parties in terms of the discourse-promise of transparency in the statements, especially after 2000, opposition parties have a clear advantage over the ruling parties.